2014
DOI: 10.3233/jad-130866
|View full text |Cite
|
Sign up to set email alerts
|

Three-Dimensional Quantitative Imaging of Telomeres in Buccal Cells Identifies Mild, Moderate, and Severe Alzheimer's Disease Patients

Abstract: Using three-dimensional (3D) telomeric analysis of buccal cells of 82 Alzheimer's disease (AD) patients and cognitively normal age and gender-matched controls, we have for the first time examined changes in the 3D nuclear telomeric architecture of buccal cells among levels of AD severity based on five 3D parameters: i) telomere length, ii) telomere number, iii) telomere aggregation, iv) nuclear volume, and v) a/c ratio, a measure of spatial telomere distribution. Our data indicate that matched controls have si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
40
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 35 publications
(47 citation statements)
references
References 67 publications
6
40
1
Order By: Relevance
“…& Though intellectual stimulation and socialization is encouraged, more studies need to be performed to determine whether these activities can be used to modify cognitive decline in those with dementia [18].…”
Section: Other Lifestyle Factorsmentioning
confidence: 99%
“…& Though intellectual stimulation and socialization is encouraged, more studies need to be performed to determine whether these activities can be used to modify cognitive decline in those with dementia [18].…”
Section: Other Lifestyle Factorsmentioning
confidence: 99%
“…The collection of patient samples was done as previously described [36]. Using Epicentre Catch-A11 sample collection swabs, buccal cells were collected by the Queen’s University Memory Clinics’ personnel in duplicates from each participant’s cheek and smeared onto a marked square of microscope VWR pre-cleaned frosted slides.…”
Section: Methodsmentioning
confidence: 99%
“…In this cohort, we described a non-invasive method to examine and define alterations in AD and during AD progression using quantitative 3D nuclear telomere imaging of buccal cells (BCs). As a follow-up to our initial cohort of 82 subjects with age- and gender-matched caregiver controls (41 AD and 41 non-AD) [36], the current study reports on a second independent patient cohort in which we investigated the 3D nuclear telomeric profiles from BCs of 88 study participants using age- and gender-matched non-caregiver controls (44 AD and 44 non-AD). This is in contrast to the previous study that was based on caregiver controls [28].…”
Section: Introductionmentioning
confidence: 99%
“…A multi-tissue study showed that calpain activity is increased in CSF and decreased in blood of AD patients [57]. Interestingly, a rare study of telomere in buccal cells showed shorter telomeres and increased number of telomeres in AD patients compared to controls [58].…”
Section: In-depth Information For Admentioning
confidence: 99%